The Influence of after Sales Service and Product Quality on the Decision to Purchase a Toyota Avanza Car in Deli Serdang - Eka Umi Kalsum; Muslim Wijaya; Roswani Siregar (LLDIKTI Wilayah 1 Sumatera Utara, 2021)
This study describes the after-sales service and product quality of purchasing a Toyota Avanza in Deli Serdang. The theory used in this study includes the idea of after-sales service, product quality, and buying decisions. The population in this study were 50 Toyota Avanza car users who passed on Jalan Sutomo, Lubuk Pakam Deli Serdang. The data analysis model used is multiple linear regression analysis. The research method uses a quantitative descriptive approach supported by a survey and is explanatory. The study results by testing the t-test hypothesis showed that after-sales service had a positive and significant effect on purchasing decisions for the Toyota Avanza in Deli Serdang. Product quality has a positive and significant impact on buying decisions for the Toyota Avanza in Deli Serdang. The results of the F test show that after-sales service and product quality have a positive and significant effect on purchasing decisions for the Toyota Avanza in Deli Serdang. The value of the coefficient of determination (R2) of after-sales service and product quality can explain the purchasing decision variables of 70.1%. The remaining 29.9% is influenced by other variables not examined in this study, such as price promotion and so on.